Analysis of Factors Influencing The Capital Buffer In Sharia Commercial Banks In Indonesia - Rizki Amalia Tanjung; Imsar Imsar; Rahmat Daim Harahap (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
Capital Buffer is the difference between the ratio of bank capital to the minimum capital adequacy ratio in accordance with central bank regulations. This study aims to determine the determinants of Capital Buffer in Islamic Commercial Banks in Indonesia in 2018-2021. This study aims to examine the effect of ROE, NPF, FDR, BOPO, and Bank Size on the Level of Capital Buffer simultaneously. The analytical method uses a quantitative research approach and uses secondary data. In this study, the analysis technique used was panel data regression with a fixed effect model using the Eviews 10 tool. Based on the results of the analysis of this study, it shows that ROE has no significant effect on Capital Buffer. FDR has no significant correlation to Capital Buffer. NPF has no significant effect on the Capital Buffer, BOPO has no significant correlation on the Capital Buffer, and Bank Size has a significant effect on the Capital Buffer. Simultaneously ROE, FDR, NPF, Bank Size, and BOPO have a significant effect on Capital Buffer. the results of the regression estimation show that the independent variable has a predictive ability of the model of 80.25%, while the remaining 19.75% is influenced by other factors outside the model.